(x+2)^2+(y-1)^2=(x+3)^2 (y-2)^2-(y+2)^2=(x+6)^2-(x-1)^2

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[TeX]
[pretty]
[text]
       2          2          2
(x + 2)  + (y - 1)  = (x + 3) 
$$\left(x + 2\right)^{2} + \left(y - 1\right)^{2} = \left(x + 3\right)^{2}$$
       2          2          2          2
(y - 2)  - (y + 2)  = (x + 6)  - (x - 1) 
$$\left(y - 2\right)^{2} - \left(y + 2\right)^{2} = - \left(x - 1\right)^{2} + \left(x + 6\right)^{2}$$
Быстрый ответ
[TeX]
$$x_{1} = - \frac{269}{98} - \frac{8 i}{49} \sqrt{10}$$
=
$$- \frac{269}{98} - \frac{8 i}{49} \sqrt{10}$$
=
-2.74489795918367 - 0.516290230231572*i

$$y_{1} = \frac{3}{7} + \frac{2 i}{7} \sqrt{10}$$
=
$$\frac{3}{7} + \frac{2 i}{7} \sqrt{10}$$
=
0.428571428571429 + 0.903507902905251*i
$$x_{2} = - \frac{269}{98} + \frac{8 i}{49} \sqrt{10}$$
=
$$- \frac{269}{98} + \frac{8 i}{49} \sqrt{10}$$
=
-2.74489795918367 + 0.516290230231572*i

$$y_{2} = \frac{3}{7} - \frac{2 i}{7} \sqrt{10}$$
=
$$\frac{3}{7} - \frac{2 i}{7} \sqrt{10}$$
=
0.428571428571429 - 0.903507902905251*i